EMPLOYEE ENGAGEMENT, COMPENSATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Jauhari, Ahmad; Pribadiyono, Pribadiyono (International Conference of Business and Social Sciences, 2023)
The issue addressed in this research focuses on the declining employee performance, which is indicated by factors such as employee engagement, compensation, and work discipline. The research was conducted at CV. Asia Paramitha, a company engaged in the distribution of agricultural pharmaceutical products in Kediri Regency. The population consisted of 89 respondents, and a sample of 53 individuals who met the criteria was obtained using purposive sampling. Data collection was conducted through a survey with a questionnaire as the primary instrument. The data were analyzed using inferential statistical methods, specifically multiple linear regression analysis to test hypotheses. The research results indicate that employee engagement has a partial, positive, and significant influence on employee performance. Compensation, on the other hand, has no significant influence on employee performance when considered separately. Work discipline, when examined separately, has a partial, positive, and significant influence on employee performance. Simultaneously, employee engagement, compensation, and work discipline have a positive and significant impact on employee performance at CV. Asia Paramitha.